KESIAPAN PSIKOLOGIS ANAK DAN ORANGTUA DALAM MENGHADAPI PEMBELAJARAN TATAP MUKA - Ervin Nurul Affrida; Isabella Hasiana (Kanigara, 2022)
Psychological preparation for face-to-face learning requires deep focus. This is because each individual has different readiness related to learning not only from parents but also from children. Therefore, assistance is needed for parents and children to be able to adapt in facing face-to-face learning. The method used in this PPM activity is lectures and discussions with parents. The result of this PPM activity is that parents have new understanding and knowledge that can be used as a reference for them how to behave psychologically in dealing with face-to-face learning. In addition, life in a family that is conducive and mutually supportive of one another will create a happy and comfortable atmosphere so that children are motivated to participate in face-to-face learning. Therefore, parents are expected to be able to control emotions, think positively, modify the environment and build positive energy.